Moderating diets to feed the future. (14th October 2014) - Davis, Kyle F.; D'Odorico, Paolo; Rulli, Maria Cristina
Abstract Population growth, dietary changes, and increasing biofuel use are placing unprecedented pressure on the global food system. While this demand likely cannot be met by expanding agricultural lands, much of the world's cropland can attain higher crop yields. Therefore, it is important to examine whether increasing crop productivity to the maximum attainable yield (i.e., yield gap closure) alone can substantially improve food security at global and national scales. Here we show that closing yield gaps through conventional technological development (i.e., fertilizers and irrigation) can potentially meet future global demand if diets are moderated and crop‐based biofuel production is limited. In particular, we find that increases in dietary demand will be largely to blame should crop production fall short of demand. In converting projected diets to a globally adequate diet (3000 kcal/cap/d; 20% animal kcal) under current agrofuel use, we find that 1.8–2.6 billion additional people can be fed in 2030 and 2.1–3.1 billion additional people in 2050, depending on the extent to which yields can improve in those periods. Therefore, the simple combination of yield gap closure and moderating diets offers promise for feeding the world's population but only if long‐term sustainability is the focus.